An Investigation of the Relationship between Receptive Skills among Moroccan High School Students - Imad Hamdanat (Magister Program of English Education, Fakultas Keguruan dan Ilmu Pendidikan Universitas Mulawarman, 2023)
As the prevalence of the English language in the Moroccan educational system continues to rise, there is a pressing need for an in-depth exploration of language development dynamics, explicitly focusing on listening comprehension and reading proficiency. This correlational study investigated the relationship between listening and reading skills among 80 high school students from Al Mansour Addahbi High School in Sidi Kacem, Morocco. The sample was selected using a simple random sampling technique. Data were collected through standardized listening and reading proficiency tests, and statistical analyses were conducted using SPSS software. The results revealed a significant positive correlation (r = 0.604, p < 0.001) between listening skills and reading skills, indicating that students with higher listening abilities also demonstrated stronger reading skills, and vice versa. Furthermore, regression analysis showed that listening skills significantly predicted reading skills (Beta = 0.604, p < 0.001), emphasizing its importance as a key predictor of reading ability. The findings contribute to the field of EFL education by emphasizing the interdependence of listening and reading skills, suggesting the need for integrated language instruction strategies. Recommendations for future research include exploring this relationship across different age groups and linguistic backgrounds and investigating the long-term impact of language instruction interventions on both skills.